Going through the labyrinth: the political economy of Argentina’s abandonment of the gold standard (1929-1933) - Pablo Gerchunoff; José Luis Machinea (CEPAL Review, 2015)
This article is the short but crucial history of four years of transition in a monetary and exchange-rate regime that culminated in 1933 with the final abandonment of the gold standard in Argentina. That process involved decisions made at critical junctures at which the government authorities had little time to deliberate and against which they had no analytical arsenal, no technical certainties and few political convictions. The objective of this study is to analyse those “decisions” at seven milestone moments, from the external shock of 1929 to the submission to Congress of a bill for the creation of the central bank and a currency control regime characterized by multiple exchange rates. The new regime that this reordering of the Argentine economy implied would remain in place, in one form or another, for at least a quarter of a century.